Design of a Novel Electrochemical Nanobiosensor for the Detection of Prostate Cancer by Measurement of PSA Using Graphene-based Materials - Fatemeh Saeidi tabar; mehrab pourmadadi; Fatemeh Yazdian; Hamid Rashedi (AUT Journal of Electrical Engineering, 2021)
In this work, an aptamer-based electrochemical nanobiosensor has been developed for early detection of prostate cancer. Prostate-specific antigen (PSA) is the most common marker of prostate cancer, and this study aimes to detect this biomarker through electrochemical nanobiosensor-based aptamer, using nanostructures Graphene Oxide/graphitic Carbon Nitride/Gold nanoparticles (GO/g-C3N4/Au NPs). The aptamer chains are stabilized on the surface of a glassy carbon electrode (GCE) by Reduced Graphene Oxide, graphitic Carbon Nitride, and Gold nanoparticles (rGO/g-C3N4/Au NPs). To ensure the correct operation of the aptamer, a selectivity analysis was taken between five substances, and an electrochemical biosensor designed with good stability and high selectivity, diagnosis the desired analyte (PSA) compared to other materials. For characterization of aptasensor Electrochemical, CV, SQW and, EIS tests were performed to investigate the features of the synthesized nanoparticles, XRD, FTIR, SEM, TEM tests were carried out, and the results indicated that the used nanoparticles were well synthesized. The limit of detection (LOD) is 1.67 pg.ml-1 in hexafrrocyanide ([Fe(CN)6]-3/-4) media, this limit of detection is much lower and demonstrates the high ability of the nanobiosensor in early detection of PSA. The designed biosensor needs a short time (about 30 min) to detect the PSA as a symptom of prostate cancer.